1989
DOI: 10.1002/jcu.1870170605
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time ultrasound evaluation of tuberculous pleural effusions

Abstract: An evaluation of 21 patients with tuberculous pleurisy was carried out to assess the role of ultrasonography in the diagnosis of tuberculous pleural effusion. Ultrasonography revealed winding structures of different lengths and thicknesses (winding bands) in 8 patients, and filiform structures of a higher echogenicity and a shorter length (linear echoes) in 13. These findings were associated with exudates having a high content of fibrin and protein, respectively, suggesting that winding bands might be formed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…In 1989 Martinez et al reported that winding bands were seen with sonography in 8 out of 21 (38%) patients with TP 18. In the present study we showed that 17 out of 87 (21.8%) patients had septation revealed by thoracic sonography.…”
Section: Discussionsupporting
confidence: 59%
“…In 1989 Martinez et al reported that winding bands were seen with sonography in 8 out of 21 (38%) patients with TP 18. In the present study we showed that 17 out of 87 (21.8%) patients had septation revealed by thoracic sonography.…”
Section: Discussionsupporting
confidence: 59%
“…4,5 Pleural thickening and a complex septated pattern, with fibrinous strands in the pleural space producing a weblike or branching appearance, has been strongly associated with tuberculosis. [6][7][8] Chen et al 9 found a 96% specificity for tuberculous pleural effusions when differentiating between tuberculosis and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, tuberculous pleural effusions and empyema commonly had complex septated sonographic appearances. 6,[13][14][15] However, the differentiation between empyema and tuberculosis is easily made. Therefore, our objective was to focus on the lymphocyte-rich exudative pleural effusions.…”
Section: D a Bmentioning
confidence: 99%